Association of sodium‐glucose cotransporter‐2 inhibitors with outcomes in type 2 diabetes with reduced and preserved left ventricular ejection fraction: Analysis from the CVD‐REAL 2 study. Issue 6 (23rd March 2021) - Lam, Carolyn S. P.; Karasik, Avraham; Melzer‐Cohen, Cheli; Cavender, Matthew A.; Kohsaka, Shun; Norhammar, Anna; Thuresson, Marcus; Chen, Hungta; Wittbrodt, Eric; Fenici, Peter; Kosiborod, Mikhail; ,
Abstract: This study of real‐world data from the Maccabi database in Israel compared the risk of heart failure hospitalization (HHF) or death in patients with type 2 diabetes (T2D) initiating sodium‐glucose cotransporter‐2 (SGLT2) inhibitors versus other glucose‐lowering drugs (OGLDs) according to baseline left ventricular (LV) ejection fraction (EF). After propensity‐matching patients by baseline EF there were 10 614 episodes of treatment initiation; 57% had diabetes for >10 years, the mean glycated haemoglobin level was 66 mmol/mol (8.2%), ∼43% had cardiovascular disease, ∼7% had heart failure and ∼ 20% had chronic kidney disease. A total of 2876 patients (∼9%) had reduced EF (<50%). Over a mean follow‐up of 1.5 years there were 371 HHFs or deaths, 88 (23.7%) in patients with reduced EF. Initiation of SGLT2 inhibitors versus OGLDs was associated with lower risk of HHF or death overall (hazard ratio [HR] 0.57, 95% confidence interval [CI] 0.46‐0.70]; P < 0.001) and in patients with both reduced EF (HR 0.61, 95% CI 0.40‐0.93) and preserved EF (HR 0.55, 95% CI 0.43‐0.70), with no significant heterogeneity ( P interaction = 0.72). Our findings from real‐world clinical practice show that the lower risk of HHF and death associated with use of SGLT2 inhibitors versus OGLDs is consistent in T2D patients with both reduced and preserved EF.